EFEKTIVITAS PROGRAM KARTU PRAKERJA DALAM MENURUNKAN PENGANGGURAN DI MASA PANDEMI COVID-19 - Mochammad Rozikin; Fiqih Widiar Oktasari (KOLABORATIF: Jurnal Isu Sosial dan Tinjauan Kebijakan, 2023)
Unemployment is a problem that is quite difficult and complicated to handle. The impact of the COVID-19 pandemic has made the government work extra in overcoming the worsening unemployment problem. This study aims to analyze the effectiveness of the implementation of the pre-employment card program carried out by the government in overcoming unemployment during the COVID-19 pandemic. This study uses a literature review approach by taking references and reference materials from various sources relevant to the topics discussed. The results showed that the pre-employment card program was considered quite effective in its implementation. Government consistency is needed in handling during the pandemic and even the post-pandemic period until the economic condition really recovers as usual.